Material design of soft biological tissue replicas using viscoelastic micromechanical modelling. (January 2022) - Estermann, Sarah-Jane; Pahr, Dieter H.; Reisinger, Andreas
Abstract: Anatomical models for research and education are often made of artificial materials that attempt to mimic biological tissues in terms of their mechanical properties. Recent developments in additive manufacturing allow tuning mechanical properties with microstructural designs. We propose a strategy for designing material microstructures to mimic soft tissue viscoelastic behaviour, based on a micromechanical Mori–Tanaka model. The model was applied to predict homogenised viscoelastic properties of materials, exhibiting a matrix-inclusion microstructure with varying inclusion volume fractions. The input properties were thereby obtained from compression relaxation tests on silicone elastomers. Validation of the model was done with experimental results for composite samples. Finally, different combinations of silicones were compared to mechanical properties of soft tissues (hepatic, myocardial, adipose, cervical, and prostate tissue), found in literature, in order to design microstructures for replicating these tissues in terms of viscoelasticity. The viscoelastic Mori–Tanaka model showed good agreement with the corresponding experimental results for low inclusion volume fractions, while high fractions lead to underestimation of the complex modulus by the model. Predictions for the loss tangent were reasonably accurate, even for higher inclusion volume fractions. Based on the model, designs for 3D printed microstructures can be extracted in order to replicate the viscoelastic properties of soft tissues.